Doença hepática gordurosa não alcoólica na deficiência congênita e isolada de GH - Araujo, Rachel Diniz Correia de (2014)
Context: Non-alcoholic fatty liver disease (NAFLD) is known to be associated with insulin resistance, atherosclerosis, and low serum IGF-I levels. We have described a large cohort of patients with isolated GH deficiency (IGHD) due to the c.57+1G→A mutation in the GHRH receptor gene. These subjects have increased insulin sensitivity (IS), delayed atherosclerosis, and normal longevity. We hypothesized that despite visceral obesity NAFLD would be absent or mild due to the increased IS. Objective: To assess the prevalence and severity of NAFLD in adult subjects with lifetime, congenital, untreated IGHD. Methods: We studied 22 IGHD adults and 25 controls (CO) matched for age and gender. NAFLD was assessed by a comprehensive liver function panel, and ultrasonographic pattern (HP) coded as 0=absent; 1=mild; 2=moderate; and 3=severe. Results: Compared to CO, IGHD individual had lower serum IGF-I (p<0.0001), higher total cholesterol (p=0.027), lower prothrombin time (p=0.017), similar activated partial thromboplastin time and fibrinogen values. ALT values were similar in the two groups, but AST was higher in IGHD (p=0.013). However, more IGHD subjects (7/22) than CO (3/23) had ALT above the upper limit of normal (p=0.044). The prevalence of NAFLD was higher in IGHD than CO (61% vs. 29%, p=0.032), and the HP score was higher in IGHD than CO (p=0.041), but severe NAFLD was not observed in any IGHD (or CO) individual. Conclusions: liver HP score is increased in lifetime untreated congenital IGHD, but the increase in transaminases is mild, suggesting lack of advanced forms of NAFLD.